An African Perspective of the Concept of Salvation in the Psalter - Ogunkunle, Caleb O. (African Journal of Evangelical Theology, 2009)
[republication] This article is the author's adaptation and re-direction of an article (“A Comparative Study of Salvation in the Psalter and African Indigenous Churches”) by him that appeared in the journal, The Living Word May-June 2009, Vol. 115, No.3 (pp.137-153).
free